2007
DOI: 10.1677/joe.1.07077
|View full text |Cite
|
Sign up to set email alerts
|

Gastric ghrelin cell development is hampered and plasma ghrelin is reduced by delayed weaning in rats

Abstract: The duration of breastfeeding has attracted much interest, as a prolonged period of breastfeeding has been shown to reduce the risk of developing obesity. The mechanism behind the reduced risk is, however, poorly understood. The novel hormone ghrelin augments appetite, promotes body weight increase and increases adiposity. The majority of circulating ghrelin emanates from endocrine cells in the oxyntic mucosa of the stomach. In newborn humans and rodents, the number of ghrelin cells is low after birth until we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…However, without any calorie increase, it is plausible that the introduction of specific dietary components in solid foods or resultant alterations in gut flora may result in epigenetic modification of metabolic programming, as shown in rodent models. [23][24][25][26] These early feeding-related changes may have lifelong detrimental effects. Other hypotheses relate to specific nutrients, for example excess protein intake in infancy may increase insulin-like growth factor-1 levels, leading to increased differentiation of preadipocytes into adipocytes, and leading to earlier age at adiposity rebound.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, without any calorie increase, it is plausible that the introduction of specific dietary components in solid foods or resultant alterations in gut flora may result in epigenetic modification of metabolic programming, as shown in rodent models. [23][24][25][26] These early feeding-related changes may have lifelong detrimental effects. Other hypotheses relate to specific nutrients, for example excess protein intake in infancy may increase insulin-like growth factor-1 levels, leading to increased differentiation of preadipocytes into adipocytes, and leading to earlier age at adiposity rebound.…”
Section: Discussionmentioning
confidence: 99%
“…For example, ghrelin is a peptide, which stimulates food intake and increases adiposity. Fak et al 24 have shown that gastric expression and plasma levels of ghrelin increase in rats at the time of introduction of solid food into their diet, and that delayed weaning is associated with reduced grehlin levels. Prenatal nutritional status and interactions with the child's early environment may have profound and prolonged effects on obesity, weight distribution and associated metabolic disease; these changes may well contribute to the array of emerging problems in developing and indigenous communities.…”
Section: Discussionmentioning
confidence: 99%
“…A recent laboratory study in rats has suggested that delayed weaning (meaning continuation of breast milk and delayed introduction of solid food) reduces plasma levels of the appetite-related peptide, ghrelin and also reduces gastric ghrelin cell development. (34) Ghrelin concentration increases during specific stages in rat infancy were formerly thought to be age as opposed to diet-related. (34) Furthermore, leptin concentrations in human breast milk have been demonstrated to inversely correlate with human infant weight gain up until 2 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…This pattern is reminiscent of gastrinproducing G-cells in rats, which are present in the pancreatic islets well before birth, but in the stomach only postnatally (Larsson et al 1976a). Furthermore, although the number of gastric ghrelin cells is maintained at lower level by delayed weaning of rat pups, the islet ghrelin cell population is unaffected (Fak et al 2007). The importance of this potential difference between the two cell populations in response to different nutrients needs further investigation.…”
Section: Ghrelin Cells In Ratsmentioning
confidence: 99%
“…Ghrelin cells are also present in rat pancreas during foetal and neonatal development , Fak et al 2007, Walia et al 2008. As in the human (Wierup et al 2002, Wierup & Sundler 2005) and mouse (Prado et al 2004, Heller et al 2005 pancreas, the rat ghrelin cells display a developmental regulation .…”
Section: Ghrelin Cells In Ratsmentioning
confidence: 99%